Effects of different models of sucrose intake on the oxidative status of the uterus and ovary of rats. - Joanna Sadowska (Public Library of Science (PLoS), 2021)
The aim of the study was to assess the effect of different models of sucrose intake on carbohydrate-lipid metabolism and changes in oxidant balance in the ovaries and uterus of rats. Animals were divided into three groups: I-basic feed, II-feed contains 8% of sucrose, III-alternately every second week the basic feed and modified feed contains 16% of sucrose. The diet containing 8% of sucrose was found to result in an increased activity of antioxidant enzymes in the blood, with unchanged malonylodialdehyde concentration. Variable sucrose administration pattern intensified oxidative stress in the blood and led to disturbed redox equilibrium in the rat uterus, even at a comparable long-term sucrose uptake as in the group II. This was manifested as a reduced superoxide dismutase activity (in the blood and uterus) and a higher malonylodialdehyde concentration (in the uterus). The changes observed could have been a result of metabolic disorders (higher amount of visceral fat, higher glucose concentration, higher index of homeostasis model assessment of insulin resistance, and reduced HDL-cholesterol concentration) and endocrine disorders (higher oestrogen concentrations). Changes in the antioxidant status in the rats kept on the alternating diet, may underpin the failure of fertilised egg implantation in the uterine tissue and pregnancy completion.